Sentimental'noe putesestvie na rodinu - Musyka russkoj zivopisi - Michalkov, Nikita Sergeevic; Karavaev, Elizbar (RUSCICO, 2006)
The author of this unique art project, Nikita Mikhalkov, presents to the viewers the works of his favorite 19th-century painters. We shall see a whole panorama of artistic trends and tastes of the period, learn about amazing life stories of the painters and their subjects, the history of creation of the masterpieces of Russian painting, and get a broad picture of Russian culture, particularly the culture of painting. Thanks to a deeply personal, involved presentation of the material, a lively, ingenuous intonation, the paintings of the talented Russian artists will come so close to us that we'll be able to hear "the music of Russian painting" and understand what perhaps was hidden due to our, sometimes superficial, momentary perception. And, as a result, get a gratifying sense of association with the unique heritage of our great country and the proud feeling of being part of its great people and history. This project is, undoubtedly, a momentous cultural and civic act, even a heroic endeavor of N. Mikhalkov, aimed at promoting the national self-consciousness. [www.ruscico.com]
Keywords: DVD-Video